Exploring the Mediated-Moderated Impact in ESG-Value Nexus: The role of Cost of Debt and Firm Size in Chinese Listed Companies - Peng, Bingxiang; Zang, Chengcheng (Journal of Ecohumanism, 2024)
Background: ESG disclosures are critical aspects of corporate reporting, reflecting an entity’s commitment towards sustainable and responsible business practices. In China, the increasing emphasis on the ESG practices tends to raise questions regarding their effect on the financial performance, specifically in case of the listed companies. Purpose: The study aims to investigate the influence of ESG disclosures and Firm Value of the Chinese listed companies, directly, as well as through the mediating effect of cost of debt and size’s moderating role. Design: The study employs a fixed-effects regression for a panel dataset, consisting of 1065 observations, developed using 213 entities and 5 fiscal years (2018 to 2022). The independent variables of the study are the individual ESG components and the aggregate ESG score while Tobin’s Q is the dependent variable. The control variables include leverage, profitability, growth, age, and liquidity. The cost of debt and size has been proxied by the interest costs and natural log of total assets respectively. Results: ESG metrics, individually or collectively, do not influence Tobin’s Q whereas the interaction effect of the size tends to influence the value negatively, only in case of the total ESG score. It states that the positive effect on market value declines as the size of the company increases. The cost of debt, on the other hand, is a significant mediator in the interaction aspect, adversely influencing Tobin’s Q. Policy Implications: The policy makers must support the smaller companies in their ESG adoption as they are more likely to benefit from the ESG practices due to their increase in the market valuation. Additionally, tailored ESG reporting as well as implementation strategies tend to maximise the financial benefits across different firm sizes. Originality/Value: The novel insights provided by the study into the complicated dynamics of the ESG and Value in case of the Chinese companies highlights varied effects. The role of firm size and the importance of cost of debt are prominent in contributing to a broader understanding of the ESG’s role in enhancing value of the enterprises.